Complex-phase alumina fiber and preparation method thereof

By using high solid content spinning sol and segmented temperature-controlled heat treatment methods, composite phase alumina fiber was prepared, which solved the problem of high mullite phase transition temperature, and improved the ceramic yield, the mechanical properties and temperature resistance of the fibers. .

CN119433758AActive Publication Date: 2025-02-14SHANDONG RES & DESIGN ACADEMY OF IND CERAMICS
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411150875.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-21
Publication Date
2025-02-14
Estimated Expiration
2044-08-21

AI Technical Summary

Technical Problem

In the existing methods for preparing composite phase alumina fibers, the mullite phase transition temperature is high, resulting in low ceramic yield and insufficient mechanical properties and temperature resistance of the fiber.

Method used

Using high-solid content spinning sol, dry spinning and segmented temperature control heat treatment methods, the components and pH of the sol are adjusted to prepare composite phase alumina fibers, with crystal phases of mullite and γ-alumina or mol Composite crystal phase of leite and α-alumina.

Benefits of technology

It improves the yield of ceramics, enhances the mechanical properties and temperature resistance of the fibers, solves the problem of high mullite phase transition temperature, and ensures the safety and environmental protection of production through chlorine-free, safe and environmentally friendly raw materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119433758A_ABST
    Figure CN119433758A_ABST
Patent Text Reader

Abstract

The invention discloses a complex-phase alumina fiber and a preparation method thereof, and belongs to the technical field of ceramic fiber, the preparation method comprises the following steps: spinning, drying and heat treatment; spinning: performing dry spinning on the alumina spinning sol to obtain alumina gel fibers; the crystal phase of the complex-phase alumina fiber is one of a composite crystal phase of mullite and gamma-alumina or a composite crystal phase of mullite and alpha-alumina; according to the preparation method disclosed by the invention, the ceramic yield is improved, the problem of high phase transition temperature of gel fiber mullite is solved, and the prepared complex-phase alumina fiber is good in mechanical property and temperature resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramic fibers, and in particular to a multiphase alumina fiber and a preparation method thereof. Background Art

[0002] Complex alumina fiber is a polycrystalline ceramic fiber with alumina and mullite as the main components. Mullite is a binary solid solution compound composed of alumina and silicon oxide. It has many excellent physical properties, such as high fracture toughness, high temperature resistance, oxidation resistance, thermal shock resistance, creep resistance, low thermal conductivity, strong electrical insulation, low dielectric constant, etc. It also has high chemical stability and good corrosion resistance in alkaline solvents and carbonate solvents. Complex alumina fiber combines the advantages of alumina fiber and mullite fiber, has higher strength and lower thermal conductivity, and performs well in high temperature oxidation resistance. In practical applications, complex phase alumina fibers can be used in a variety of fields, for example: used for high-temperature industrial furnace insulation, which can effectively extend the life of the furnace and improve production efficiency; used in the production of other polycrystalline mullite insulation materials, such as raw materials for boards, paper, vacuum-formed parts, etc.; used in the preparation of reinforced metal-based composite materials, such as high-load mechanical parts, high-temperature and high-speed rotating parts, and high-function components with lightweight requirements, specifically automobile connecting rods, transmission rods, brake pads, and helicopter transmission devices; used in the preparation of reinforced resin-based composite materials and ceramic-based composite materials, such as high-performance radar antenna covers; used in coating materials, it can increase the material's thermal shock resistance, oxidation resistance, high-temperature corrosion resistance, etc.

[0003] Chinese patent CN114773070B discloses a method for preparing alumina continuous fibers using carboxylate aluminum sol as a precursor, wherein aluminum hydroxide dispersion is used as an aluminum source, a small molecule carboxylic acid is added to obtain carboxylate aluminum sol, and then silica sol and a spinning aid are added to prepare alumina fibers through dry spinning and sintering; however, the mullite phase transition temperature is high.

[0004] Chinese patent CN114162844B discloses a precursor composite sol for alumina / mullite dual-phase fiber and a preparation method thereof, wherein aluminum powder and organic acid are used as raw materials to prepare carboxylate aluminum sol, and then acidified silica sol is added to prepare mullite spinning sol, and alumina / mullite dual-phase fiber is obtained by dry spinning and sintering; however, aluminum powder is used in the preparation, and aluminum powder is an explosive chemical.

[0005] Chinese patent CN113860862A discloses a low-cost method for preparing mullite fiber, using aluminum hydroxide and small molecule carboxylic acid as raw materials to prepare aluminum carboxylate sol, then adding silicon source to obtain spinning sol, and then dry spinning and sintering to obtain mullite fiber. However, the solid content of spinning sol is low, the fiber loses a lot of weight during the sintering process, and a large amount of organic matter volatilizes, which will cause holes and defects on the surface and inside of the fiber, reducing the mechanical properties of the fiber. Summary of the invention

[0006] In view of the deficiencies in the prior art, the present invention provides a multiphase alumina fiber and a preparation method thereof, which improves the ceramic yield and solves the problem of high phase transition temperature of gel fiber mullite. The prepared multiphase alumina fiber has good mechanical properties and temperature resistance.

[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows: A method for preparing a composite alumina fiber, comprising the following steps: spinning, drying, and heat treatment; The spinning comprises dry spinning the alumina spinning sol to obtain alumina gel fibers; In the spinning, the sol temperature during dry spinning is 30-50°C, the tunnel temperature is 60-100°C, and the spinning speed is 100-500m / min; The drying is to dry the alumina gel fiber to obtain dried alumina gel fiber; In the drying process, the drying temperature is 50-80°C and the drying time is 1-3h; The heat treatment is to heat the dried alumina gel fiber to 650-750°C at a heating rate of 3-5°C / min and keep the temperature for 50-70min; and heat the dried alumina gel fiber to 1100-1300°C at a heating rate of 5-8°C / min and keep the temperature for 60-120min to obtain a composite alumina fiber. The crystal phase of the multiphase alumina fiber is one of a composite crystal phase of mullite and γ-alumina or a composite crystal phase of mullite and α-alumina; When the crystal phase of the multiphase alumina fiber is a composite crystal phase of mullite and γ-alumina, the preparation method of the alumina spinning sol in the spinning is: adding a No. 1 single-phase mullite sol precursor to a No. 2 aluminum sol, stirring at room temperature for 30-40 minutes; and then vacuum concentrating for 1-1.5 hours to obtain the alumina spinning sol; When the crystal phase of the multiphase alumina fiber is a composite crystal phase of mullite and γ-alumina, in the preparation of the alumina spinning sol in the spinning, the mass ratio of the No. 1 single-phase mullite sol precursor to the No. 2 aluminum sol is 2-3:1; The temperature of the vacuum concentration is 40-60°C and the vacuum degree is 0-0.03MPa; The method for preparing the No. 1 single-phase mullite sol precursor comprises the following steps: preparing a single-phase mullite sol stock solution, and heating and activating it; The method for preparing the single-phase mullite sol stock solution comprises dissolving aluminum nitrate in water and stirring at room temperature until dissolved; then adding aluminum isopropoxide and stirring at room temperature for 5-30 minutes; then adding tetraethyl orthosilicate and stirring at room temperature for 1-3 hours; then heating to 50-80° C. and stirring for reaction for 3-5 hours to obtain the single-phase mullite sol stock solution; In the preparation of the single-phase mullite sol stock solution, the molar ratio of aluminum isopropoxide to aluminum nitrate is 2.5-3.5:1; The aluminum to silicon molar ratio is 2.8-3.2:1; The molar ratio of aluminum nitrate to water is 1:30-50; The temperature-raising activation is to raise the temperature of the single-phase mullite sol stock solution to 70-90°C at a heating rate of 5-8°C / min and keep it for 5-8h, which is the solvent removal process; and to raise the temperature to 100-120°C at a heating rate of 3-5°C / min and keep it for 3-5h to obtain a single-phase mullite sol precursor No. 1; The preparation method of the No. 2 aluminum sol comprises the following steps: preparing aluminum carboxylate stock solution and activating it; The method for preparing the aluminum carboxylate stock solution comprises heating deionized water to 70-90° C., adding aluminum hydroxide, stirring for 15-30 min, adding monocarboxylic acid and dicarboxylic acid, stirring for 15-30 min, heating to boiling at a heating rate of 15-25° C. / min, reflux at the temperature for 5-10 h, cooling, filtering, and taking the filtrate to obtain the aluminum carboxylate stock solution; In the preparation of the aluminum carboxylate stock solution, the monocarboxylic acid is one of formic acid, acetic acid, and propionic acid; The dicarboxylic acid is one of oxalic acid, malonic acid and succinic acid; The molar ratio of aluminum hydroxide, monocarboxylic acid and dicarboxylic acid is 1:0.5-1:2.5-3.5; The molar ratio of aluminum hydroxide to deionized water is 1:20-40; The activation in the preparation of the No. 2 aluminum sol is as follows: the carboxylate aluminum stock solution is heated to 80-100°C at a heating rate of 5-8°C / min and maintained for 5-8h; the temperature is heated to 100-150°C at a heating rate of 3-5°C / min and maintained for 3-5h to obtain a No. 1 aluminum sol precursor; 1 part by weight of the No. 1 aluminum sol precursor is dispersed in 1.5-2.5 parts by weight of water to obtain No. 1 aluminum sol; then the No. 1 aluminum sol is heated to 150-250°C at 3-5°C / min and maintained for 3-5h to obtain a No. 2 aluminum sol precursor, and 1 part by weight of the No. 2 aluminum sol precursor is dispersed in 1.5-2.5 parts by weight of water to obtain No. 2 aluminum sol; When the crystal phase of the multiphase alumina fiber is a composite crystal phase of mullite and α-alumina, the preparation method of the alumina spinning sol in the spinning is: mixing No. 1 activated silica sol and No. 1 aluminum sol, reacting at 40-60° C. for 3-5 hours, adding a spinning aid, stirring at room temperature for 30-60 minutes, and then vacuum concentrating for 1 hour to obtain the alumina spinning sol; When the crystal phase of the multiphase alumina fiber is a composite crystal phase of mullite and α-alumina, in the preparation of the alumina spinning sol in the spinning, the mass ratio of No. 1 activated silica sol to No. 1 aluminum sol is 1:2.3-3.5; The spinning aid is one of polyethylene glycol, polyvinyl alcohol and polyethylene oxide; The mass fraction of the spinning aid is 1-3%; The temperature of the vacuum concentration is 40-60°C and the vacuum degree is 0-0.03MPa; The preparation method of the No. 1 activated silica sol is as follows: adding a small molecule carboxylic acid to the silica sol to adjust the pH to 3-4, stirring at 30-50° C. for 30-60 minutes to obtain the No. 1 activated silica sol; In the preparation of the activated silica sol No. 1, the mass content of silicon dioxide in the silica sol is 30-40%; The small molecule carboxylic acid is one of formic acid, acetic acid and propionic acid; The preparation method of the No. 1 aluminum sol comprises the following steps: preparing aluminum carboxylate stock solution and activating it; The method for preparing the aluminum carboxylate stock solution in the preparation of the No. 1 aluminum sol is the same as the method for preparing the aluminum carboxylate stock solution in the preparation of the No. 2 aluminum sol.

[0008] In the activation process of the preparation of the No. 1 aluminum sol, the carboxylate aluminum solution is heated to 80-100°C at a heating rate of 5-8°C / min and maintained for 5-8h; the temperature is heated to 100-150°C at a heating rate of 3-5°C / min and maintained for 3-5h to obtain the No. 1 aluminum sol precursor; 1 part by weight of the No. 1 aluminum sol precursor is dispersed in 1.5-2.5 parts by weight of water to obtain the No. 1 aluminum sol.

[0009] A composite alumina fiber obtained by the aforementioned preparation method.

[0010] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention adopts chlorine-free, safe and environmentally friendly raw materials to prepare multiphase alumina fibers, uses high solid content spinning sol, improves the ceramic yield, and solves the problem of high phase transition temperature of gel fiber mullite. The composition and pH of the sol are adjusted by staged temperature control, and the obtained multiphase alumina fibers have good temperature resistance; (2) By adjusting the heat treatment temperature, the present invention can obtain a composite alumina fiber with a crystal phase of mullite and γ-alumina and a composite alumina fiber with a crystal phase of mullite and α-alumina, respectively. The ceramic conversion rate of the composite alumina fiber with a crystal phase of mullite and γ-alumina is 45-47%, and the density of the ceramic fiber at 1100°C is 3.1 g / cm 3 The tensile strength of the bundle is 1.8-1.9GPa. After heat treatment at 1100℃ for 5h in air, the fiber strength retention is 80-85%. The ceramic conversion rate of the obtained composite alumina fiber with mullite and α-alumina is 47-48%, and the density of the ceramic fiber at 1300℃ is 3.2-3.3g / cm 3 The tensile strength of the bundle is 2.2-2.3GPa. After heat treatment at 1200℃ in air for 5h, the fiber strength retention is 80-85%. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] Figure 1 This is the XRD spectrum of the complex phase alumina fiber obtained in Example 4. DETAILED DESCRIPTION

[0012] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, the specific implementation methods of the present invention are now described.

[0013] Example 1 A method for preparing a multiphase alumina fiber, specifically comprising: 1. Preparation of Aluminum Sol Aluminum hydroxide, monocarboxylic acid and dicarboxylic acid are used as raw materials to prepare aluminum sol; specifically: (1) Preparation of aluminum carboxylate stock solution: heat deionized water to 70°C, add aluminum hydroxide, stir for 15 min, add formic acid and malonic acid, stir for 15 min, heat to boiling at a rate of 15°C / min, keep reflux for 5 h, cool, filter, and take the filtrate to obtain aluminum carboxylate stock solution; The molar ratio of aluminum hydroxide, formic acid, and malonic acid is 1:1:3.5; The molar ratio of aluminum hydroxide to deionized water is 1:20; (2) Activation: The temperature of the aluminum carboxylate stock solution is controlled in stages to adjust the composition of the aluminum carboxylate to obtain an aluminum sol; specifically: The carboxylate aluminum stock solution is heated to 80°C at a heating rate of 5°C / min and maintained for 5 hours. This stage is the process of removing excess carboxylic acid; the temperature is raised to 100°C at a heating rate of 3°C / min and maintained for 3 hours to obtain No. 1 aluminum sol precursor; 1 part by weight of No. 1 aluminum sol precursor is dispersed in 1.5 parts by weight of water to obtain No. 1 aluminum sol, and then the No. 1 aluminum sol is heated to 150°C at 3°C / min and maintained for 3 hours to obtain No. 2 aluminum sol precursor, and 1 part by weight of No. 2 aluminum sol precursor is dispersed in 1.5 parts by weight of water to obtain No. 2 aluminum sol; The average molecular weight of aluminum carboxylate in the aluminum sol precursor No. 1 is 175 g / mol; The average molecular weight of aluminum carboxylate in the No. 2 aluminum sol precursor is 155 g / mol; The pH of the No. 1 aluminum sol is 3; The pH of the No. 2 aluminum sol is 4; 2. Preparation of single-phase mullite sol A single-phase mullite sol is prepared using aluminum isopropoxide, tetraethyl orthosilicate and aluminum nitrate as raw materials; specifically: (1) Preparation of a single-phase mullite sol stock solution: dissolve aluminum nitrate in water and stir at room temperature until dissolved; then add aluminum isopropoxide and stir at room temperature for 5 minutes; then add ethyl orthosilicate and stir at room temperature for 1 hour; then heat to 50°C and stir for 3 hours to obtain a single-phase mullite sol stock solution; The molar ratio of aluminum isopropoxide to aluminum nitrate is 2.5:1; The aluminum to silicon molar ratio is 2.8:1; The molar ratio of aluminum nitrate to water is 1:30; (2) Heating activation: The temperature of the single-phase mullite sol stock solution is controlled in stages to adjust the components to obtain a mullite sol precursor; specifically: The single-phase mullite sol stock solution was heated to 70°C at a heating rate of 5°C / min and maintained for 5 hours, which was the solvent removal process; the temperature was raised to 100°C at a heating rate of 3°C / min and maintained for 3 hours to obtain a single-phase mullite sol precursor No. 1; 3. Preparation of Sol The single-phase mullite sol precursor No. 1 is added to the aluminum sol No. 2, the mass ratio of the single-phase mullite sol precursor No. 1 to the aluminum sol No. 2 is 2:1, and the mixture is stirred at room temperature for 30 minutes; then, the mixture is vacuum concentrated at a temperature of 40° C. and a vacuum degree of 0 MPa for 1 hour to obtain an alumina spinning sol; The viscosity of the alumina spinning sol is 30 Pa.s; 4. Spinning and heat treatment (1) Spinning: Dry spinning alumina spinning sol to obtain alumina gel fiber. The sol temperature during dry spinning is 30°C, the tunnel temperature is 60°C, and the spinning speed is 100 m / min. (2) Drying: Drying the alumina gel fiber in a blast oven at 50°C for 1 h to obtain dry alumina gel fiber; (3) Heat treatment: The dried alumina gel fiber was heated to 650°C at a heating rate of 3°C / min and kept at this temperature for 50 min; the dried alumina gel fiber was heated to 1100°C at a heating rate of 5°C / min and kept at this temperature for 60 min to obtain a composite alumina fiber with a crystalline phase of mullite and γ-alumina. The ceramic conversion rate of the composite alumina fiber is 45%, and the density of the ceramic fiber at 1100℃ is 3.1g / cm 3 The tensile strength of the bundle is 1.8 GPa, and after heat treatment at 1100 ° C in air for 5 hours, the fiber strength retention is 81%.

[0014] This embodiment also provides a complex phase alumina fiber obtained by the aforementioned preparation method.

[0015] Example 2 A method for preparing a multiphase alumina fiber, specifically comprising: 1. Preparation of Aluminum Sol Aluminum hydroxide, monocarboxylic acid and dicarboxylic acid are used as raw materials to prepare aluminum sol; specifically: (1) Preparation of aluminum carboxylate stock solution: heat deionized water to 75°C, add aluminum hydroxide, stir for 20 min, add formic acid and malonic acid, stir for 20 min, heat to boiling at a rate of 20°C / min, keep reflux for 6 h, cool, filter, and take the filtrate to obtain aluminum carboxylate stock solution; The molar ratio of aluminum hydroxide, formic acid, and malonic acid is 1:0.6:2.7; The molar ratio of aluminum hydroxide to deionized water is 1:25; (2) Activation: The temperature of the aluminum carboxylate stock solution is controlled in stages to adjust the composition of the aluminum carboxylate to obtain an aluminum sol; specifically: The carboxylate aluminum stock solution is heated to 85°C at a heating rate of 6°C / min and maintained for 5.5 hours. This stage is the process of removing excess carboxylic acid; the temperature is raised to 120°C at a heating rate of 4°C / min and maintained for 3.5 hours to obtain No. 1 aluminum sol precursor; 1 part by weight of No. 1 aluminum sol precursor is dispersed in 1.8 parts by weight of water to obtain No. 1 aluminum sol, and then the No. 1 aluminum sol is heated to 180°C at 4°C / min and maintained for 3.5 hours to obtain No. 2 aluminum sol precursor, and 1 part by weight of No. 2 aluminum sol precursor is dispersed in 1.8 parts by weight of water to obtain No. 2 aluminum sol; The average molecular weight of aluminum carboxylate in the aluminum sol precursor No. 1 is 172 g / mol; The average molecular weight of aluminum carboxylate in the No. 2 aluminum sol precursor is 150 g / mol; The pH of the No. 1 aluminum sol is 3.3; The pH of the No. 2 aluminum sol is 4.6; 2. Preparation of single-phase mullite sol A single-phase mullite sol is prepared using aluminum isopropoxide, tetraethyl orthosilicate and aluminum nitrate as raw materials; specifically: (1) Preparation of a single-phase mullite sol stock solution: dissolve aluminum nitrate in water and stir at room temperature until dissolved; then add aluminum isopropoxide and stir at room temperature for 30 minutes; then add tetraethyl orthosilicate and stir at room temperature for 3 hours; then heat to 80°C and stir for 5 hours to obtain a single-phase mullite sol stock solution; The molar ratio of aluminum isopropoxide to aluminum nitrate is 3.5:1; The aluminum to silicon molar ratio is 3.2:1; The molar ratio of aluminum nitrate to water is 1:50; (2) Heating activation: The temperature of the single-phase mullite sol stock solution is controlled in stages to adjust the components to obtain a mullite sol precursor; specifically: The single-phase mullite sol stock solution was heated to 90°C at a heating rate of 8°C / min and maintained for 8 hours, which was the solvent removal process; the temperature was raised to 120°C at a heating rate of 5°C / min and maintained for 5 hours to obtain single-phase mullite sol precursor No. 1; 3. Preparation of Sol The single-phase mullite sol precursor No. 1 was added to the aluminum sol No. 2, the mass ratio of the single-phase mullite sol precursor No. 1 to the aluminum sol No. 2 was 3:1, and the mixture was stirred at room temperature for 40 minutes; then, the mixture was vacuum concentrated at a temperature of 60° C. and a vacuum degree of 0.03 MPa for 1.5 hours to obtain an alumina spinning sol; The viscosity of the alumina spinning sol is 34 Pa.s; 4. Spinning and heat treatment (1) Spinning: Dry spinning alumina spinning sol to obtain alumina gel fiber. The sol temperature during dry spinning is 40°C, the tunnel temperature is 70°C, and the spinning speed is 200 m / min. (2) Drying: Drying the alumina gel fiber in a 65°C forced air oven for 2 h to obtain dry alumina gel fiber; (3) Heat treatment: The dried alumina gel fiber was heated to 700°C at a heating rate of 4°C / min and kept at this temperature for 60 min; the dried alumina gel fiber was heated to 1100°C at a heating rate of 6°C / min and kept at this temperature for 80 min to obtain a composite alumina fiber with the crystal phases of mullite and γ-alumina. The ceramic conversion rate of the composite alumina fiber is 47%, and the density of the ceramic fiber at 1100℃ is 3.1g / cm 3 The tensile strength of the bundle is 1.9 GPa, and after heat treatment at 1100 ° C in air for 5 hours, the fiber strength retention is 83%.

[0016] This embodiment also provides a complex phase alumina fiber obtained by the aforementioned preparation method.

[0017] Example 3 A method for preparing a multiphase alumina fiber, specifically comprising: 1. Preparation of Aluminum Sol Aluminum hydroxide, monocarboxylic acid and dicarboxylic acid are used as raw materials to prepare aluminum sol; specifically: (1) Preparation of aluminum carboxylate stock solution: heat deionized water to 85°C, add aluminum hydroxide, stir for 25 minutes, add acetic acid and oxalic acid, stir for 25 minutes, heat to boiling at a heating rate of 22°C / min, keep reflux for 9 hours, cool, filter, and take the filtrate to obtain aluminum carboxylate stock solution; The molar ratio of aluminum hydroxide, acetic acid, and oxalic acid is 1:0.9:3.3; The molar ratio of aluminum hydroxide to deionized water is 1:35; (2) Activation: The temperature of the aluminum carboxylate stock solution is controlled in stages to adjust the composition of the aluminum carboxylate to obtain an aluminum sol; specifically: The aluminum carboxylate stock solution was heated to 95°C at a heating rate of 7°C / min and maintained for 7.5 hours, which is the process of removing excess carboxylic acid; the temperature was raised to 140°C at a heating rate of 5°C / min and maintained for 4 hours to obtain No. 1 aluminum sol precursor; 1 part by weight of No. 1 aluminum sol precursor was dispersed in 2.5 parts by weight of water to obtain No. 1 aluminum sol; The average molecular weight of aluminum carboxylate in the aluminum sol precursor No. 1 is 168 g / mol; The pH of the No. 1 aluminum sol is 3.7; 2. Preparation of activated silica sol: Take silica sol with a mass content of 30% of silica, add small molecule carboxylic acid to adjust the pH to 3, stir at 30°C for 30 minutes, and obtain activated silica sol No. 1; The small molecule carboxylic acid is formic acid; 3. Preparation of sol: Mix activated silica sol No. 1 with aluminum sol No. 1, the mass ratio of activated silica sol No. 1 to aluminum sol No. 1 is 1:2.3, react at 40°C for 3h, add 1% spinning aid by mass, stir at room temperature for 30min, and then vacuum concentrate at 40°C and vacuum degree of 0MPa for 1h to obtain alumina spinning sol; The spinning aid is polyethylene glycol; The viscosity of the alumina spinning sol is 30 Pa.s; 4. Spinning and heat treatment (1) Spinning: The alumina spinning sol is dry-spun to obtain alumina gel fibers. The sol temperature of the dry spinning is controlled to be 45°C, the tunnel temperature is controlled to be 90°C, and the spinning speed is controlled to be 400 m / min.

[0018] (2) Drying: drying the alumina gel fiber in a blast oven at 70°C for 2.5 h to obtain dried alumina gel fiber; (3) Heat treatment: The dried alumina gel fiber was heated to 720°C at a heating rate of 4.5°C / min and kept at this temperature for 60 min. Then, the temperature was heated to 1300°C at a heating rate of 7.5°C / min and kept at this temperature for 110 min to obtain a composite alumina fiber with the crystalline phases of mullite and α-alumina.

[0019] The ceramic conversion rate of the composite alumina fiber is 47%, and the density of the ceramic fiber at 1300℃ is 3.2g / cm 3 The tensile strength of the bundle is 2.2 GPa, and after heat treatment at 1200 ° C in air for 5 hours, the fiber strength retention is 81%.

[0020] This embodiment also provides a complex phase alumina fiber obtained by the aforementioned preparation method.

[0021] Example 4 A method for preparing a multiphase alumina fiber, specifically comprising: 1. Preparation of Aluminum Sol Aluminum hydroxide, monocarboxylic acid and dicarboxylic acid are used as raw materials to prepare aluminum sol; specifically: (1) Preparation of aluminum carboxylate stock solution: heat deionized water to 90°C, add aluminum hydroxide, stir for 30 min, add formic acid and malonic acid, stir for 30 min, heat to boiling at a rate of 25°C / min, keep reflux for 10 h, cool, filter, and take the filtrate to obtain aluminum carboxylate stock solution; The molar ratio of aluminum hydroxide, formic acid and malonic acid is 1:0.5:2.5; The molar ratio of aluminum hydroxide to deionized water is 1:40; (2) Activation: The temperature of the aluminum carboxylate stock solution is controlled in stages to adjust the composition of the aluminum carboxylate to obtain an aluminum sol; specifically: The aluminum carboxylate stock solution is heated to 100°C at a heating rate of 8°C / min and maintained for 8 hours, which is the process of removing excess carboxylic acid; the temperature is raised to 150°C at a heating rate of 5°C / min and maintained for 5 hours to obtain No. 1 aluminum sol precursor; 1 part by weight of No. 1 aluminum sol precursor is dispersed in 2.5 parts by weight of water to obtain No. 1 aluminum sol; The average molecular weight of aluminum carboxylate in the aluminum sol precursor No. 1 is 175 g / mol; The pH of the No. 1 aluminum sol is 4; 2. Preparation of activated silica sol: Take silica sol with a mass content of 40% of silica, add small molecule carboxylic acid to adjust the pH to 4, stir at 50°C for 60 minutes, and obtain activated silica sol No. 1; The small molecule carboxylic acid is acetic acid; 3. Preparation of sol: Mix activated silica sol No. 1 with aluminum sol No. 1, the mass ratio of activated silica sol No. 1 to aluminum sol No. 1 is 1:3.5, react at 60°C for 5h, add 3% spinning aid by mass, stir at room temperature for 60min, and then vacuum concentrate at 60°C and vacuum degree of 0.03MPa for 3h to obtain alumina spinning sol; The spinning aid is polyvinyl alcohol; The viscosity of the alumina spinning sol is 50 Pa.s; 4. Spinning and heat treatment (1) Spinning: Dry spinning alumina spinning sol to obtain alumina gel fiber. The sol temperature during dry spinning is 50°C, the tunnel temperature is 100°C, and the spinning speed is 500 m / min. (2) Drying: Drying the alumina gel fiber in a forced air oven at 80°C for 3 h to obtain dry alumina gel fiber; (3) Heat treatment: The dried alumina gel fiber was heated to 750°C at a heating rate of 5°C / min and kept at this temperature for 70 min; the dried alumina gel fiber was heated to 1300°C at a heating rate of 8°C / min and kept at this temperature for 120 min to obtain a composite alumina fiber with the crystal phases of mullite and α-alumina. The obtained composite alumina fiber was subjected to XRD test, and the obtained XRD spectrum is shown in Figure 1 As shown; The ceramic conversion rate of the composite alumina fiber is 48%, and the density of the ceramic fiber at 1300℃ is 3.3g / cm 3 The tensile strength of the bundle is 2.3 GPa, and after heat treatment at 1200 ° C in air for 5 hours, the fiber strength retention is 80%.

[0022] This embodiment also provides a complex phase alumina fiber obtained by the aforementioned preparation method.

[0023] Comparative Example 1 On the basis of Example 1, the step (2) of heating activation in the step (2) of preparing the single-phase mullite sol is omitted. Accordingly, the single-phase mullite sol stock solution obtained in the step (1) of preparing the single-phase mullite sol stock solution is directly used in the step (3) of preparing the sol to replace the single-phase mullite sol precursor No. 1 in equal amounts.

[0024] The problems existing in the preparation of this comparative example are: the solid content of the alumina spinning sol obtained in the sol preparation step in step 3 is relatively low, resulting in reduced spinnability in the spinning and heat treatment in step 4, and also affecting the ceramic conversion rate of the obtained multiphase alumina fiber, reducing the ceramic conversion rate to 37%.

[0025] Comparative Example 2 On the basis of Example 4, the activation step (2) in the step (1) of preparing the aluminum sol is omitted, and accordingly, the aluminum carboxylate stock solution obtained in the step (1) of preparing the aluminum carboxylate stock solution is directly used in the step (3) of preparing the sol to replace the aluminum sol No. 1 in equal amounts; The second step of activating the silica sol is omitted, and accordingly, the silica sol having a mass content of 40% of silicon dioxide is directly used in the third step of preparing the sol to replace the activated silica sol No. 1 in equal amounts; The problem in the preparation of this comparative example is that since the aluminum sol and the silica sol are not activated, the activities of the aluminum sol and the silica sol are low, and a clear and spinnable alumina spinning sol is not obtained in the third step of preparing the sol.

[0026] Unless otherwise specified, all percentages used in the present invention are by mass.

[0027] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a multiphase alumina fiber, characterized in that: The process consists of the following steps: spinning, drying, and heat treatment; The spinning comprises dry spinning the alumina spinning sol to obtain alumina gel fibers; The crystal phase of the multiphase alumina fiber is one of a composite crystal phase of mullite and γ-alumina or a composite crystal phase of mullite and α-alumina; When the crystal phase of the multiphase alumina fiber is a composite crystal phase of mullite and γ-alumina, the preparation method of the alumina spinning sol in the spinning is: adding a No. 1 single-phase mullite sol precursor to a No. 2 aluminum sol, stirring at room temperature for 30-40 minutes; and then vacuum concentrating for 1-1.5 hours to obtain the alumina spinning sol; When the crystal phase of the complex alumina fiber is a composite crystal phase of mullite and α-alumina, the preparation method of the alumina spinning sol in the spinning is: mixing No. 1 activated silica sol with No. 1 aluminum sol, reacting at 40-60°C for 3-5h, adding a spinning aid, stirring at room temperature for 30-60min, and then vacuum concentrating for 1h to obtain the alumina spinning sol.

2. The method for preparing the multiphase alumina fiber according to claim 1, characterized in that: The method for preparing the No. 1 single-phase mullite sol precursor comprises the following steps: preparing a single-phase mullite sol stock solution, and heating and activating it; The method for preparing the single-phase mullite sol stock solution comprises dissolving aluminum nitrate in water and stirring at room temperature until dissolved; then adding aluminum isopropoxide and stirring at room temperature for 5-30 minutes; then adding tetraethyl orthosilicate and stirring at room temperature for 1-3 hours; then heating to 50-80° C. and stirring for reaction for 3-5 hours to obtain the single-phase mullite sol stock solution; In the preparation of the single-phase mullite sol stock solution, the molar ratio of aluminum isopropoxide to aluminum nitrate is 2.5-3.5:1; The aluminum to silicon molar ratio is 2.8-3.2:1; The molar ratio of aluminum nitrate to water is 1:30-50; The temperature-raising activation is to raise the temperature of the single-phase mullite sol stock solution to 70-90°C at a heating rate of 5-8°C / min and keep it for 5-8h, which is the solvent removal process; and to raise the temperature to 100-120°C at 3-5°C / min and keep it for 3-5h to obtain No. 1 single-phase mullite sol precursor.

3. The method for preparing the multiphase alumina fiber according to claim 1, characterized in that: The preparation method of the No. 2 aluminum sol comprises the following steps: preparing aluminum carboxylate stock solution and activating it; In the activation process of the preparation of the No. 2 aluminum sol, the carboxylate aluminum stock solution is heated to 80-100°C at a heating rate of 5-8°C / min and maintained for 5-8h; the temperature is heated to 100-150°C at a heating rate of 3-5°C / min and maintained for 3-5h to obtain a No. 1 aluminum sol precursor; 1 part by weight of the No. 1 aluminum sol precursor is dispersed in 1.5-2.5 parts by weight of water to obtain No. 1 aluminum sol; then the No. 1 aluminum sol is heated to 150-250°C at 3-5°C / min and maintained for 3-5h to obtain a No. 2 aluminum sol precursor, and 1 part by weight of the No. 2 aluminum sol precursor is dispersed in 1.5-2.5 parts by weight of water to obtain No. 2 aluminum sol.

4. The method for preparing the multiphase alumina fiber according to claim 1, characterized in that: The preparation method of the No. 1 activated silica sol is as follows: adding a small molecule carboxylic acid to the silica sol to adjust the pH to 3-4, stirring at 30-50° C. for 30-60 minutes to obtain the No. 1 activated silica sol; In the preparation of the activated silica sol No. 1, the mass content of silicon dioxide in the silica sol is 30-40%; The small molecule carboxylic acid is one of formic acid, acetic acid and propionic acid.

5. The method for preparing the multiphase alumina fiber according to claim 3, characterized in that: The preparation method of the No. 1 aluminum sol comprises the following steps: preparing aluminum carboxylate stock solution and activating it; In the activation process of the preparation of the No. 1 aluminum sol, the carboxylate aluminum solution is heated to 80-100°C at a heating rate of 5-8°C / min and maintained for 5-8h; the temperature is heated to 100-150°C at a heating rate of 3-5°C / min and maintained for 3-5h to obtain the No. 1 aluminum sol precursor; 1 part by weight of the No. 1 aluminum sol precursor is dispersed in 1.5-2.5 parts by weight of water to obtain the No. 1 aluminum sol.

6. The method for preparing the multiphase alumina fiber according to claim 1, characterized in that: The heat treatment is to heat the dried alumina gel fiber to 650-750°C at a heating rate of 3-5°C / min and keep it warm for 50-70min; and to heat it to 1100-1300°C at a heating rate of 5-8°C / min and keep it warm for 60-120min to obtain a composite alumina fiber.

7. The method for preparing the multiphase alumina fiber according to claim 1, characterized in that: When the crystal phase of the multiphase alumina fiber is a composite crystal phase of mullite and γ-alumina, in the preparation of the alumina spinning sol in the spinning, the mass ratio of the No. 1 single-phase mullite sol precursor to the No. 2 aluminum sol is 2-3:1; The temperature of the vacuum concentration is 40-60° C. and the vacuum degree is 0-0.03 MPa.

8. The method for preparing the multiphase alumina fiber according to claim 1, characterized in that: When the crystal phase of the multiphase alumina fiber is a composite crystal phase of mullite and α-alumina, in the preparation of the alumina spinning sol in the spinning, the mass ratio of No. 1 activated silica sol to No. 1 aluminum sol is 1:2.3-3.5; The spinning aid is one of polyethylene glycol, polyvinyl alcohol and polyethylene oxide; The mass fraction of the spinning aid is 1-3%; The temperature of the vacuum concentration is 40-60° C. and the vacuum degree is 0-0.03 MPa.

9. The method for preparing the multiphase alumina fiber according to claim 5, characterized in that: In the preparation of the No. 2 aluminum sol and the No. 1 aluminum sol, an aluminum carboxylate stock solution is prepared, deionized water is heated to 70-90° C., aluminum hydroxide is added, stirred for 15-30 min, monocarboxylic acid and dicarboxylic acid are added, stirred for 15-30 min, heated to boiling at a heating rate of 15-25° C. / min, kept at reflux for 5-10 h, cooled, filtered, and the filtrate is taken to obtain an aluminum carboxylate stock solution; In the preparation of the aluminum carboxylate stock solution, the monocarboxylic acid is one of formic acid, acetic acid, and propionic acid; The dicarboxylic acid is one of oxalic acid, malonic acid and succinic acid; The molar ratio of aluminum hydroxide, monocarboxylic acid and dicarboxylic acid is 1:0.5-1:2.5-3.5; The molar ratio of aluminum hydroxide to deionized water is 1:20-40.

10. A multiphase alumina fiber obtained by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Preparation method of low-cost mullite fiber

    CN113860862A

  • A precursor composite sol for alumina / mullite biphase fibers and its preparation method

    CN114162844B

  • A method for preparing continuous alumina fibers using aluminum carboxylate sol as a precursor

    CN114773070B

  • Low-density high-performance alumina-based ceramic fiber and preparation method thereof

    CN106609404A

  • Mullite-based complex phase fibers and preparation method thereof

    CN107473749A